NOX4 Mediates Pseudomonas aeruginosa-Induced Nuclear Reactive Oxygen Species Generation and Chromatin Remodeling in Lung Epithelium - Panfeng Fu; Ramaswamy Ramchandran; Tara Sudhadevi; Prasanth P. K. Kumar; Yashaswin Krishnan; Yuru Liu; Yutong Zhao; Narasimham L. Parinandi; Anantha Harijith; Junichi Sadoshima; Viswanathan Natarajan (MDPI AG, 2021)
Pseudomonas aeruginosa (PA) infection increases reactive oxygen species (ROS), and earlier, we have shown a role for NADPH oxidase-derived ROS in PA-mediated lung inflammation and injury. Here, we show a role for the lung epithelial cell (LEpC) NOX4 in PA-mediated chromatin remodeling and lung inflammation. Intratracheal administration of PA to Nox4flox/flox mice for 24 h caused lung inflammatory injury; however, epithelial cell-deleted Nox4 mice exhibited reduced lung inflammatory injury, oxidative stress, secretion of pro-inflammatory cytokines, and decreased histone acetylation. In LEpCs, NOX4 was localized both in the cytoplasmic and nuclear fractions, and PA stimulation increased the nuclear NOX4 expression and ROS production. Downregulation or inhibition of NOX4 and PKC δ attenuated the PA-induced nuclear ROS. PA-induced histone acetylation was attenuated by Nox4-specific siRNA, unlike Nox2. PA stimulation increased HDAC1/2 oxidation and reduced HDAC1/2 activity. The PA-induced oxidation of HDAC2 was attenuated by N-acetyl-L-cysteine and siRNA specific for Pkc δ, Sphk2, and Nox4. PA stimulated RAC1 activation in the nucleus and enhanced the association between HDAC2 and RAC1, p-PKC δ, and NOX4 in LEpCs. Our results revealed a critical role for the alveolar epithelial NOX4 in mediating PA-induced lung inflammatory injury via nuclear ROS generation, HDAC1/2 oxidation, and chromatin remodeling.